The therapeutic effects of curcumin and capsaicin against cyclophosphamide side effects on the uterus in rats - Yilmaz,Ercan (2018)
Abstract Purpose: To evaluate the impact of systemic cyclophosphamide treatment on the rat uterus and investigate the potential therapeutic effects of natural antioxidant preparations curcumin and capsaicin against cyclophosphamide side effects. Methods: A 40 healthy adult female Wistar albino rats were used in this study. Rats were randomly divided into four groups to determine the effects of curcumin and capsaicin against Cyclophosphamide side effects on the uterus (n=10 in each group); Group 1 was the control group (sham-operated), Group 2 was the cyclophosphamide group, Group 3 was the cyclophosphamide + curcumin (100mg/kg) group, and Group 4 was the cyclophosphamide + capsaicin (0.5 mg/kg) group. Results: Increased tissue oxidative stress and histological damage in the rat uterus were demonstrated due to the treatment of systemic cyclophosphamide chemotherapy alone. The level of tissue oxidant and antioxidant markers and histopathological changes were improved by the treatment of curcumin and capsaicin. Conclusion: Cytotoxic effects of natural alkylating chemotherapeutic agents like cyclophosphamide on the uterus can be prevented by curcumin and capsaicin.